Measurement of anesthetic pollution in veterinary operating rooms for small animals: Isoflurane pollution in a university veterinary hospital - Figueiredo, Drielle B.S. [UNESP] (2021)
Introduction: Inhaled anesthetics are used worldwide for anesthesia maintenance both in human and veterinary operating rooms. High concentrations of waste anesthetic gases can lead to health risks for the professionals exposed. Considering that anesthetic pollution in a veterinary surgical center in developing countries is unknown, this study aimed, for the first time, to measure the residual concentration of isoflurane in the air of operating rooms for small animals in a Brazilian university hospital. Method: Residual isoflurane concentrations were measured by an infrared analyzer at the following sites: corner opposite to anesthesia machine; breathing zones of the surgeon, anesthesiologist, and patient (animal); and in front of the anesthesia machine at three time points, that is, 5, 30 and 120 minutes after anesthesia induction. Results: Mean residual isoflurane concentrations gradually increased in the corner opposite to anesthesia machine and in the breathing zones of the surgeon and the anesthesiologist (p < 0.05). There was an increase at 30 minutes and 120 minutes when compared to the initial time points in the animal's breathing zone, and in the front of the anesthesia machine (p < 0.05). There was no significant difference at measurement sites regardless of the moment of assessment. Conclusion: This study reported high residual isoflurane concentrations in veterinary operating rooms without an exhaust system, which exceeds the limit recommended by an international agency. Based on our findings, there is urgent need to implement exhaust systems to reduce anesthetic pollution and decrease occupational exposure.